Epithelial to Mesenchymal Transition: A Mechanism that Fuels Cancer Radio/Chemoresistance - József Dudás; Andrea Ladányi; Julia Ingruber; Teresa Bernadette Steinbichler; Herbert Riechelmann (Cells, 2020)
Epithelial to mesenchymal transition (EMT) contributes to tumor progression, cancer cell invasion, and therapy resistance. EMT is regulated by transcription factors such as the protein products of the SNAI gene family, which inhibits the expression of epithelial genes. Several signaling pathways, such as TGF-beta1, IL-6, Akt, and Erk1/2, trigger EMT responses. Besides regulatory transcription factors, RNA molecules without protein translation, micro RNAs, and long non-coding RNAs also assist in the initialization of the EMT gene cluster. A challenging novel aspect of EMT research is the investigation of the interplay between tumor microenvironments and EMT. Several microenvironmental factors, including fibroblasts and myofibroblasts, as well as inflammatory, immune, and endothelial cells, induce EMT in tumor cells. EMT tumor cells change their adverse microenvironment into a tumor friendly neighborhood, loaded with stromal regulatory T cells, exhausted CD8+ T cells, and M2 (protumor) macrophages. Several EMT inhibitory mechanisms are instrumental in reversing EMT or targeting EMT cells. Currently, these mechanisms are also significant for clinical use.